Surface bio-sensor based on terahertz Bragg fiber. (7th October 2021) - Shi, Jia; Tian, Linlin; Su, Mengya; Chen, Hongli; Bai, Hua; Yang, Xiang; Xiao, Zhitao; Xu, Wei; Liu, Yu; Yang, Xiaojun; Guo, Cuijuan; Xu, Degang; et al.
Abstract: Hollow-core photonic Bragg fibers have a wide range of sensing applications. In this paper, a hollow-core photonic Bragg fiber with a defect layer for surface bio-sensing is proposed and analyzed for bacterium detection in the terahertz (THz) frequency range. The hollow core is surrounded by a periodic sequence of high/low refractive index multilayers including the photosensitive resin and air. The analytes are deposited on the inner surface of the hollow-core THz Bragg fiber. The performance of the proposed sensor is numerically investigated. The result shows that the proposed surface bio-sensor provides a high core power fraction. The confinement loss of the sensor takes on two peaks in the frequency range of 0.3–0.4 and 0.45–0.55 THz, respectively. The distinguishable characteristic frequencies of the sensor are obtained with different bacterium deposited on the inner surface of the THz Bragg fiber. Furthermore, the thickness-independent surface sensing can be realized in the high frequency range. The proposed surface bio-sensor based on THz Bragg fiber can be used to recognize the kind of the bacterium and has a great potential in microorganism detections.